2015
DOI: 10.1584/jpestics.d14-031
|View full text |Cite
|
Sign up to set email alerts
|

The cross-resistance patterns and biochemical characteristics of an imidacloprid-resistant strain of the cotton aphid

Abstract: The imidacloprid-resistant strain of Aphis gossypii (RF 60 ) was further selected with imidacloprid to establish the more resistant strain (RF 75 ). After the selection for 15 generations, the resistance ratio relative to the susceptible strain increased from 66.60 to 72.60. The RF 75 strain showed different levels of cross-resistance to all the insecticides tested. Synergistic and metabolic enzyme assays suggested that carboxylesterase and cytochrome P450 may play important roles in the imidacloprid resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…THIA was highly toxic to house flies than IMI, and this agrees with Saeed et al (2017) who stated that THIA was more effective to the susceptible population of cotton leaf hopper, Amrasca devastans (Distant) than IMI. Although this result disagree with Chen et al (2015) who showed that IMI exhibited high toxicity to both RF75 and SS strains of Aphis gossypii than THIA. Additionally, the IMIresistant strain of A. gossypii at the 45 th generation did not develop cross-resistance to the second generation of neonicotinoid (THIA) Shi et al (2011).…”
Section: Discussioncontrasting
confidence: 94%
“…THIA was highly toxic to house flies than IMI, and this agrees with Saeed et al (2017) who stated that THIA was more effective to the susceptible population of cotton leaf hopper, Amrasca devastans (Distant) than IMI. Although this result disagree with Chen et al (2015) who showed that IMI exhibited high toxicity to both RF75 and SS strains of Aphis gossypii than THIA. Additionally, the IMIresistant strain of A. gossypii at the 45 th generation did not develop cross-resistance to the second generation of neonicotinoid (THIA) Shi et al (2011).…”
Section: Discussioncontrasting
confidence: 94%
“…19 Cytochrome P450-mediated imidacloprid resistance was reported in several insect species, including Aedes aegypti, 20 Musca domestica, 21,22 Bemisia tabaci, [23][24][25] N. lugens, [26][27][28][29] Laodelphax striatellus, 30 M. persicae, 12,31 and A. gossypii. 32 Single or multiple P450 genes were over-expressed in imidacloprid-resistant strains and/or populations of these insect species. Synergistic and metabolic enzyme assays in an IM-R strain of A. gossypii (RF75) suggested that cytochrome P450 may play important roles in imidacloprid resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic mechanisms in insects against synthetic and natural xenobiotics include cytochrome P450 monooxygenases (cytochrome P450s), esterases [especially carboxylesterases (CarEs)], and glutathione S‐transferases (GSTs) . Cytochrome P450‐mediated imidacloprid resistance was reported in several insect species, including Aedes aegypti , Musca domestica , Bemisia tabaci , N. lugens , Laodelphax striatellus , M. persicae , and A. gossypii . Single or multiple P450 genes were over‐expressed in imidacloprid‐resistant strains and/or populations of these insect species.…”
Section: Introductionmentioning
confidence: 99%
“…General (α and β) esterases and carboxylesterase are major enzymes accountable for the metabolism or detoxification of toxins (Li et al, 2007). The increased detoxification activities of the enzymes could weaken the defense responses of house flies to insecticides (Chen et al, 2015). Treatment of Cx.…”
Section: General Esterases (α-And β-Esterases)mentioning
confidence: 99%